COMPARATIVE STUDY OF EMERGING DISEASES OF BANANA IN MAHARASHTRA AND BURHANPUR AREA OF MADHYA PRADESH (Journal of Plant Disease Sciences, 2024)
Banana cultivation in Maharashtra faces significant challenges due to various diseases adversely affecting yield and quality of banana. This study presents a comparative analysis of four major diseases namely Sigatoka leaf spot, Cucumber Mosaic Virus (CMV), Rhizome rot and Stem pitting(blast) disease across banana plantation in Maharashtra and Burhanpur over the period of two years i.e. 2021-22 and 2022-23. Data from 138 orchards in Maharashtra and 15 orchards in Burhanpur for 2022-2023 and 122 orchards in Maharashtra and 12 orchards in Burhanpur for 2021-2022 were analysed. The study across 2021-22 and 2022-23 revealed that Pachora, Raver, Yawal and Burhanpur consistently showed high average incidences of Sigatoka leaf spot disease (up to 22.05%), and CMV (up to 65.76%). Muktainagar consistently exhibited notable average incidences of Rhizome Rot (up to 8.57%), while Raver and Bhusaval displayed significant average incidences of Stem Pitting / Blast (up to 3.82% and 1.2%, respectively). This study is useful to decide management strategy forcontrol of these diseases.
Keywords: Banana; Emerging diseases; Survey; Maharashtra state